2021
DOI: 10.1002/cam4.4237
|View full text |Cite
|
Sign up to set email alerts
|

Alitretinoin in the treatment of cutaneous T‐cell lymphoma

Abstract: Introduction In this survey, we analyzed data from patients suffering from the most common cutaneous T‐cell lymphomas (CTCLs) subtypes mycosis fungoides (MF) and Sézary syndrome (SS), treated with the retinoid alitretinoin during a 7‐year period at our outpatient department between 2015 and 2020. Materials and Methods We analyzed patient medical records including TNMB stage, side effects under therapy with alitretinoin, time to next treatment (TTNT), and previous photo documentation. Results A total of 35 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The use of retinoids for the treatment of CTCLs is well established. In previous retrospective studies investigating alitretinoin treatment in CTCLs, response rates were reported to be favourable, and side-effects were minimal ( 4 6 ). Overall, alitretinoin demonstrated efficacy in treating MFPP, as it exhibited a significant improvement in disease severity ( Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The use of retinoids for the treatment of CTCLs is well established. In previous retrospective studies investigating alitretinoin treatment in CTCLs, response rates were reported to be favourable, and side-effects were minimal ( 4 6 ). Overall, alitretinoin demonstrated efficacy in treating MFPP, as it exhibited a significant improvement in disease severity ( Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Oral bexarotene, the only approved retinoid for the treatment of cutaneous T-cell lymphomas (CTCLs), has a high frequency of adverse effects and is unavailable in certain countries, including Korea. Oral alitretinoin, approved for chronic recalcitrant hand eczema with positive outcomes and minimal side-effects, ( 2 , 3 ) has shown promising results in the treatment of MF ( 4 6 ), as well as in MFPP ( 7 ).…”
mentioning
confidence: 99%
“…Aside from bexarotene, there is a precedent to further investigate the use of other retinoid compounds to treat CTCL. One retrospective analysis examined the efficacy of oral alitretinoin for the treatment of MF and SS [ 266 , 267 ]. In one of the analyses 40 MF and 8 SS patients were recruited and were treated with 30 mg dose of oral alitretinoin achieving moderate success [ 266 ].…”
Section: The Use Of Retinoids For Skin Cancer Treatmentmentioning
confidence: 99%
“…In one of the analyses 40 MF and 8 SS patients were recruited and were treated with 30 mg dose of oral alitretinoin achieving moderate success [ 266 ]. Based on these findings, Alitretinoin is used in select counties where bexarotene is not available (e.g., Canada) as an off-label treatment for CTCL [ 267 ]. The cost of alitretinoin is significantly cheaper in comparison to bexarotene.…”
Section: The Use Of Retinoids For Skin Cancer Treatmentmentioning
confidence: 99%
“…the constatation of its efficacy in pathologies ranging from mycosis fungoides and cutaneous T-cell lymphomas8 to prurigo nodularis,9 hypertrophic lichen planus 10. This pan-retinoid achieves an immune modulation through the activation of the three isoforms (alfa, beta, gamma) of both the RAR and RXR intranuclear receptors.…”
mentioning
confidence: 99%